Fabrikasi dan Karakterisasi Produk Stir-Squeeze Casting Komposit Daur Ulang Aluminium dengan Variasi Temperatur - Gunawan, Gunawan; Bahar, Ricky Ramadhan; Saputra, M. A. Ade (Jurnal Rekayasa Mesin, 2022)
AMC (Aluminum Matrix Composites) is a type of metal composite material with aluminum as its matrix and Fly Ash as reinforced or reinforcement of the Aluminum matrix. The method used to manufacture aluminum composites is the stir-squeeze casting method, using the parameters of pouring temperature 700, 750, 800⁰C, fraction weight of fly ash 12% and constant stirring speed of 350rpm and stirring time of 3 minutes. This test includes testing of hardness, impact, chemical composition (XRF), XRD, Density and ScanningElectron Micropskop (SEM), hardness values increased from 88Al12FA alloys with 700, 750, 800⁰C temperatures with a value of 117,971, 107,982 and 116,612 BHN, decreasing the impact value of each addition of the fly ash alloy material but at a temperature of 800akC the impact strength increased, the impact value was obtained in 88Al12FA with a temperature of 700⁰C of 15,954 joules, in 88Al12FA with temperaur of 750⁰C of 14,392 joules and in 88Al12FA with a temperature of 800⁰C of 17,185 joules. The results of chemical composition (XRF) are still many impurity factors at the time of casting. XRDresults have 4 peak list aluminum and 2 peak lists from other phases. The trend test results tend to increase as the percentage of pouring temperature increases. The SEM results revealed dimple, voids and debris in each specimen.